2011 IEEE Global Telecommunications Conference - GLOBECOM 2011 2011
DOI: 10.1109/glocom.2011.6133999
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Backhauling Power Consumption on the Deployment of Heterogeneous Mobile Networks

Abstract: Energy efficiency in cellular mobile radio networks has recently gained great interest in the research community. The development of more energy efficient hardware and software components aside, effect of different deployment strategies on energy efficiency are also studied in the literature. The latter mainly consist of optimizing the number and the location of different types of base stations in order to minimize the total power consumption. Usually, in the literature, the total network power consumption is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
123
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 10 publications
0
123
0
1
Order By: Relevance
“…1, the total power consumption in the whole network consists of not only the power consumption of the BSs but also the power consumed by the backhaul [22], [23]. In the following, we discuss about those two power-consumption modellings.…”
Section: B Power Consumption Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1, the total power consumption in the whole network consists of not only the power consumption of the BSs but also the power consumed by the backhaul [22], [23]. In the following, we discuss about those two power-consumption modellings.…”
Section: B Power Consumption Modelmentioning
confidence: 99%
“…Let P (BH) k denote the backhauling power of the downlink from CCS to a k-th type BS. Following the same approach as in [22] with the assumption of identical downlink interfaces and switches at the BSs, P (BH) k can be given by…”
Section: ) Power Consumption Of Bsmentioning
confidence: 99%
“…For example, it has been shown that the total power consumption of a HetNet deployment to a large degree is affected not only by the presence of the backhaul [2] but also by its specific technological and architectural choices [3]. This means that backhaul networks take a share of the cost and of the energy consumption of mobile networks.…”
Section: Introductionmentioning
confidence: 99%
“…The key rationale behind a HetNet deployment is to provide user coverage via macro base stations (BSs) and to guarantee high capacity to costumers only where needed via the ad hoc deployment of small cells, i.e., micro, pico, and/or femto BSs. HetNets have a number of advantages, which include reduced energy consumption both in indoor [1] and in outdoor [2] deployments. In fact, small cells consume less power than macro BSs.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms provided means of determining optimal traffic allocation for 2G/3G networks considering low or high traffic scenarios. Heterogeneous networks settings are also presented in [14], wherein the authors presented a different power consumption model which takes account the back haul power for energy efficiency analysis of different cellular base stations scenarios. The authors in [15] presented a power consumption model to study and compare SISO and MIMO systems for different wireless access networks, as a function of their range,power consumption, and energy efficiency, using suburban area setting.…”
Section: Introductionmentioning
confidence: 99%